Water surface profile modelling for Pinjarra flood diversion channel and economic evaluation - Khalil, Kamal (Curtin University, 2007)
Shire of Murray has concerns regarding the negative impact that a 100 year flood could have on existing structures built before 1997. The increase cost in construction due to landfill has an adverse effect on development in Pinjarra. Feasibility of constructing a diversion channel at upstream of Murray River to attenuate the flood level from 1 in 100 year ARI to 1 in 50 year ARI, was investigated by Kiong (2003). The Murray River Water Surface Profile along three kilometres south of Greenlands Road was modelled. Flood damages on each flood occurrence were assessed and Average Annual Damage (AAD) was calculated. The AAD is used to estimate the monetary benefit against the construction cost of the diversion channel. Groundwater along Greenlands and Fauntleroy Drains was also modelled to determine the viable depth of the designed channel, as well as the analysis of backwater. The proposed channel is designed at different scenarios (invert level at breakout point, culvert or causeway design, and diversion channel variations). The benefit cost ratio of the proposed diversion channel is calculated. Other mitigation options are suggested including detention basins for structural measure, or building a new flood-proof township for non-structural measure.